New X-ray powder diffraction data and Rietveld refinement for Gd2O3 monodispersed fine spherical particles - Pires, Ana Maria [UNESP]; Davolos, Marian Rosaly [UNESP]; Paiva-Santos, C. O.; Stucchi, Elizabeth Berwerth [UNESP]; Flor, J. (Elsevier B.V., 2003)
Nominally pure Gd2O3 C-form structure from basic carbonate fine spherical particles and its differences concerning the XRD data among literature patterns using Rietveld method is reported. Gd2O3: Eu3+ from basic carbonate and Gd2O3 from oxalate were also investigated. All samples, except the one from oxalate precursor, are narrow sized, 100-200 nm. Only non-doped Gd2O3 from basic carbonate presents XRD data with smaller d(hkl) values than the literature ones. From Rietveld refinement, non-doped Gd2O3 from basic carbonate has the smallest crystallite size and from oxalate shows the greatest one. Also, the unit cell parameters indicate a plan contraction of the Gd2O3 from basic carbonate. The presence of Eu3+ increases crystallite size when basic carbonate precursor is used to prepare Gd2O3 and avoids plan contraction. The structural differences observed among Gd2O3 samples obtained are related to the type of precursor and to the presence or not of doping ion. (C) 2003 Elsevier B.V. (USA). All rights reserved.
Keywords: gadolinium oxide; europium(III); Gd2O3 : Eu3+; precursor; luminescent material; basic carbonate